Morphological Characteristic of Placenta in Sudanese Subjects - Nugud, Motaz Abd El Rahman (مجلة الجزيرة للعلوم الصحية; مجلد 10 عدد 2 (2014), 2014)
The placenta is the most important and the only organ between mother and fetus, serving multiple functions endocrinal, respiratory, metabolic and main useful functions. Normal development of a placenta is the one of the important requirements for a healthy pregnancy, regulating fetal growth and fetal health. The objectives of this study were to compare the placental weight with the infant’s weight, to measure the placental diameter and to count the number of cotyledons in each placenta. The study was carried out among 240 infants, 102 females and 138 males, delivered at Omdurman new (Alsaudi) and Alshaikh Mohammed Ali Fadol hospitals of obstetrics and gynecology. All infants were looked healthy and their weight ranged from (1.85 - 4.18 kg) with mean of 3.02. The weight of placenta ranged between (0.35 - 0.77 kg) with mean of 0.535 kg. Placental weight in males ranged between (0.35 - 0.75 kg) with mean of 0.537 kg, while the female placental weight ranged between (0.4 - 0.77 kg) with mean of 0.531 kg. The placental diameter ranged between (15 - 23 cm) with mean 18.64 cm. The diameter in males ranged between (16 - 23 cm) with mean 18.52 cm. In female was ranged from (15 - 23 cm) with mean of 18.81 cm. The mean of cotyledons number was 19 with std. Deviation 1.362 and ranged from 16 to 22. The mean of number in males was 19.17 and ranged from (16 - 22) and in females the mean was 18.88 and ranged from (16 - 22). According to Pearson, Kendall's Taub and Spearman’s correlations found that there is a significant relationship between infant weight and placental weight.